Preparation of people with autism for thyroid scintigraphy - Glumbić, Nenad; Đorđević, Mirjana; Brojčin, Branislav; Matović, Milovan (Specijalna edukacija i rehabilitacija, 2022)
Autism is a neurodevelopmental disorder that is often accompanied by various co-morbid conditions, among other things, thyroid diseases. One of the frequently used diagnostic methods to determine the appearance and function of the thyroid gland is scintigraphy. Although thyroid scintigraphy is routinely performed at Clinics for Nuclear Medicine, preparation for nuclear imaging can be very complex from the perspective of people with autism and the experts who support them. Many people with autism have trypanophobia (fear of needles), which is why they have to be specially prepared for venipuncture, during which radiopharmaceutical is injected into the organism. In addition, nuclear imaging with a gamma camera, though completely painless, can be very demanding for a patient with autism who must remain still, without speaking and vocalising during the entire imaging. Clinical staff may also face difficulties in implementing all other stages of this diagnostic procedure. Therefore, this paper proposes a set of evidence-based interventions that can be used to prepare people with autism for thyroid scintigraphy. Techniques of gradual exposure, extinction, reinforcement, modelling, and writing social stories, belonging to the category of focused interventions for people with autism, are proposed.
Keywords: autism; thyroid gland; nuclear imaging